PENDIDIKAN KARAKTER DALAM KUMPULAN CERITA PENDEK IHWAL NAMA MAJID PUCUK KARYA T. AGUS KHAIDIR - Iskandar, Surya; Suhardi; Dwi Leoni, Tessa; Zaitun; Leo Shanty, Isnaini; Wahyusari, Ahada (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines a published short story that has received the best award among other short stories selected by Kompas, and the short story